Supramolecular approach for enhancing single-molecule magnet properties of Terbium(III)-Phthalocyaninato Double-Decker complexes with crown moieties - Horii, Yoji; Damjanović, Marko; Enders, Markus (Chemistry - a European journal, 2018)
A TbIII-phthalocyaninato double-decker ([1]0) single-molecule magnet (SMM) having four 15-crown-5 moieties in one of the ligands was synthesized, and its dimerization and magnetic properties were studied in an attempt to utilize the supramolecular aggregation for enhancing the SMM properties. Aggregation of [1]0 to form [12K4]4+ in the presence of K+ ions was studied by using UV/Vis-NIR absorption and NMR spectroscopies. For the magnetic measurements, [1]0 and [12K4]4+ were dispersed in poly(methyl methacrylate) (PMMA). UV/Vis-NIR absorption measurements on the PMMA dispersed samples were used to track the formation of [12K4]4+. Direct current (DC) magnetic susceptibility measurements revealed that there were ferromagnetic Tb-Tb interactions in [12K4]4+, whereas there was no indication of ferromagnetic interactions in [1]0. Upon the formation of [12K4]4+ from [1]0 and K+ ions, the temperature at which the magnetic hysteresis occurred increased from 7 to 15 K. In addition, the area of magnetic hysteresis became larger for [12K4]4+, meaning that SMM properties of [12K4]4+ are superior to those of [1]0. Alternating current (AC) magnetic measurements were used to confirm this observation. Magnetic relaxation times at 2 K increased 1000-fold upon dimerization of [1]0 to [12K4]4+, demonstrating the effectiveness of using K+ ions to induce dimer formation for the improvement of the SMM properties.
First published: 19 December 2017
Gesehen am 04.09.2018